Effect of magnesium supplementation in improving hyperandrogenism, hirsutism, and sleep quality in women with polycystic ovary syndrome: A randomized, placebo‐controlled clinical trial. Issue 1 (29th December 2022) - Gholizadeh‐Moghaddam, Mahsa; Ghasemi‐Tehrani, Hatav; Askari, Gholamreza; Jaripur, Mahsima; Clark, Cain C. T.; Rouhani, Mohammad Hossein
Abstract: Background and Aims: Polycystic ovary syndrome (PCOS) is one of the common endocrine disorders in women, which causes numerous symptoms in women. The relationship of many micronutrients with this syndrome has been investigated. This study was conducted to examine the effects of magnesium supplementation on hyperandrogenism, hirsutism, and sleep quality in women with PCOS. Methods: In this parallel randomized clinical trial, 64 women with PCOS were randomly assigned to the magnesium group ( n  = 32) or placebo group ( n  = 32) for 10 weeks. Patients in the magnesium group received one 250 mg magnesium oxide tablet, per day. Hyperandrogenism, hirsutism, and sleep quality were measured at the beginning and end of the study. This randomized clinical trial was registered at https://www.IRCT.ir (IRCT20130903014551N8). Results: Magnesium supplementation had no significant effect on hyperandrogenism ( p  = 0.51 for dehydroepiandrosterone sulfates, p  = 0.27 for testosterone), hirsutism ( p  = 0.23), and sleep quality ( p  = 0.85) compared with placebo. Conclusions: The present study showed that a single dose of magnesium supplementation elicited no beneficial effects on the mentioned symptoms in polycystic women. It is possible that the positive effects of magnesium observed in the former studies were due to the synergistic effects of other vitamins or minerals. More studies are needed in this area.